Juxtaposing pedagogical paradigms: the efficacy of peer-assisted learning (PAL) versus faculty-assisted learning (FAL) in the refinement of surgical proficiency - Santhosh Thekkoot Vijayan; Jithin Joshy Kattuparambil; Praveen Thichur Mani; Ravindran Chirukandath; Manoj Antony (BMC Medical Education)
Abstract Background Skill training in medical education poses significant challenges. The traditional “see one, do one " approach is increasingly seen as outdated and inconsistent with modern adult learning principles. The 2019 Medical Council of India (MCI) skill training module recommends Peyton’s four-step method for psychomotor skill training is designed for a 1:1 teacher-to-student ratio. However, this ratio is often impractical due to faculty shortages. Peer-assisted learning (PAL) has emerged as a potential solution, yet its effectiveness in teaching suturing skills using Peyton’s method remains underexplored in our context. Objectives To compare the effectiveness of PAL using Peyton’s method with faculty-assisted learning (FAL) for surgical skill training and to evaluate students’ perceptions of their learning experiences through validated feedback forms. Materials and methods Sixty second-year MBBS students were randomized into two groups: one trained in basic suturing techniques (interrupted, vertical mattress, and continuous suturing) by peer tutors (PAL group) and the other by faculty members (FAL group). Peer tutors, trained by senior faculty members, used Peyton’s four-step method to teach suturing techniques in a skill lab using manikins. Post-training, proficiency was assessed using a 15-point OSCE checklist, and students’ perceptions were evaluated through a questionnaire. Results Both groups achieved mean proficiency scores exceeding 80% (> 12/15) across all techniques, with no statistically significant difference between groups. Students in both groups reported high satisfaction with their training experience. Notably, the PAL group demonstrated significantly higher confidence in performing suturing both in the skill lab and on real patients (p < 0.05). Conclusion Peer-assisted learning is as effective as faculty-assisted learning for surgical skill training using Peyton’s method. PAL can be recommended as a viable adjunct to traditional teaching methods for skill instruction. Clinical trial number Not applicable.